Civil society organizations and managerialism: On the depoliticization of the adaptive management agenda - Gutheil, Lena; Koch, Dirk-Jan (Development Policy Review, 2022)
Motivation In the last decade, a movement formed around making aid delivery more adaptive, relying on principles such as context sensitivity, flexibility, and ownership. The approaches seem promising for civil society organizations (CSOs) to fulfil their mission of fostering social transformation. While several donor agencies have started engaging with such approaches, the authors hardly see their political implications in practice. Purpose The article aims to provide evidence on an adaptive project and demonstrate how the social transformative and political nature of adaptive development management is rendered technical and depoliticized in practice. Methods and approach We use a case study of a development programme based on a social transformative policy framework that is implemented through CSOs in Uganda and Vietnam. Data were collected by means of interviews, participant observation and document analysis. Findings We find that, in practice, the social transformative policy framework is competing with managerial logics. We compare this process with the depoliticization of the Paris Declaration on Aid Effectiveness, finding striking similarities. By using practice theory, we show how managerialism remains the dominant paradigm in the civil society aid sector, fuelling the “anti-politics machine.” Policy implications The article shows that policy frameworks do not always work as intended. Donors should therefore not only change policy frameworks, but also start addressing institutional and operational requirements.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/dpr.12630

Capacity Development in a Participatory Adaptive Programme: the Case of the Clarissa Consortium - Widmer, Mireille; Apgar, Marina; Afroze, Jiniya; Malla, Sudhir; Healey, Jill; Constant, Sendrine (Institute of Development Studies, 2022)
Doing development differently rests on deliberate efforts to reflect and learn, not just about what programmes are doing and achieving, but about how they are working. This is particularly important for an action research programme like Child Labour: Action- Research-Innovation in South and South-Eastern Asia (CLARISSA), which is implemented by a consortium of organisations from across the research and development spectrum, during a rapidly changing global pandemic. Harnessing the potential of diverse skills and complementary strengths across partners in responding to the complex challenge of the worst forms of child labour, requires capacity to work together in novel ways. This Research and Evidence Paper documents how CLARISSA approached capacity development, and what we learnt from our challenges and successes. From the start, the programme incorporated a capacity development strategy resting on self-assessment of a wide range of behavioural and technical competencies that were deemed important for programme implementation, formal training activities, and periodic review of progress through an after-action review (AAR) process. An inventory of capacity development activities that took place during the first year of implementation reveals a wide range of additional, unplanned activities, enabled by the programme’s flexibility and adaptive management strategy. These are organised into eight modalities, according to the individual or collective nature of the activity, and its sequencing – namely, whether capacity development happens prior to, during, or after (from) implementation. We conclude with some reflections on the emergent nature of capacity development. Planning capacity development in an adaptive programme provides a scaffolding in terms of time, resources, and legitimacy that sustains adaptiveness. We also recognise the gaps that remain to be addressed, particularly on scaling up individual learning to collective capabilities, and widening the focus from implementation teams to individuals working at consortium level.
Accepted: 2022-04-25T10:25:54Z

Nimble adaptation: Tailoring monitoring, evaluation, and learning methods to provide actionable data in complex environments - Serpe, Lauren; Ingram, Mason; Byom, Kate (New Directions for Evaluation, 2022)
This chapter examines good practices in implementing effective Monitoring, Evaluation, and Learning (MEL) systems within complex international development Democracy, Human Rights, and Governance (DRG) programs, which are characterized by challenges of non-linearity, limited evidence of theories of change, and contextual and politically contingent nature of outcomes. The chapter presents three cases of MEL systems in complex projects implemented by Pact across distinct and diverse operating contexts – Zimbabwe, Cambodia, and Somalia – to illustrate those projects’ MEL approaches that enabled continuous adaptation. The authors analyze the cases to respond to two questions: (1) What are the key elements of effective adaptive management-focused MEL systems in complex environments? (2) What is practical guidance for designing and enabling complexity-responsive and effective adaptive management-focused MEL systems? The case studies illustrate three key elements: (1) Information gathering that closely links context, research, and performance data; (2) Systems for reflection that offer scheduled learning moments of varying frequency and intensity, as well as multiple feedback mechanisms; and (3) Enabling structures that promote adaptive mindsets and attitudes within project teams.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1002/ev.20523

The Difference Learning Makes - Factors that enable and inhibit adaptive programming - Gray, Stephen; Carl, Andy (Christian Aid, 2022)
Executive Summary When Christian Aid (CA) Ireland devised its multi-country and multi-year Irish Aid funded Programme Grant II (2017-2022), they opted to move away from a linear programme management approach and to explore an adaptive one. Across seven countries: Angola, Colombia, El Salvador, Guatemala, Israel and the occupied Palestinian territory, Sierra Leone, and Zimbabwe, CA and partner organisations support marginalised communities to realise their rights, reduce violence and address gender inequality. Since 2019, Adapt Peacebuilding has accompanied CA Ireland, CA country teams and partner organisations as they experimented with using a deliberate adaptive approach. The authors were also asked to follow up on an initial study by CA Ireland and Overseas Development Institute in 2018, which described the rationale for adopting this new approach and included early lessons from its first year of implementation. The aim of this study is to help deepen CA Ireland, CA country teams’ and partners’ understanding of (a) whether their application of adaptive programming has resulted in better development outcomes, and (b) how they can better understand the factors that enabled or inhibited the effectiveness of using this approach. Over the past three years, this study has found evidence and multiple examples that show adaptive programming contributed to better development outcomes. The main reasons cited were that these were made possible both from improvements to programming strategies based on proactive reflection and learning, as well as those that stem from the reactive capacity of adaptive programmes to change course in response to unanticipated changes in operating conditions. This study found that adaptive programming has enabled better development practice where organisations are enhancing their skills to better respond and be flexible to contextual challenges. 72% of partners surveyed described adaptive programming as the most useful approach to programme management that they have used. The programme approach has meant that CA and partner staff were better able to explore the significance of change in the context and their contributions to them. It also enabled spaces for meaningful engagement with communities in learning and programme planning processes and encouraged opportunities for experimentation in programming. The study also found that adaptive programming has supported flexible delivery. This led to better outcomes that would not have been possible were the programme not able to make flexible adjustments. The main focus has been the analysis of nine factors that can determine the effectiveness and impact (or otherwise) of using an adaptive approach, flagging important issues for understanding. These factors are identified as: 1) Leadership; 2) Organisational culture; 3) Conceptual understanding; 4) Staff capacities; 5) Partnership approaches; 6) Participation; 7) Methods and tools; 8) Administrative procedures; and 9) The operating context. Together these can provide an analytical framework for assessing an organisation’s ‘adaptive scope’, which can be used as a tool for better understanding an organisation’s potential to generate improved development outcomes via adaptive programming and how to strengthen them. The study concludes with several recommendations for CA Ireland, all of which have relevance for a broader community of donors and implementing organisations interested in the potential of adaptive programming.

Seeing the Combined Effects of Aid Programmes - Burge, Richard; Nadelman, Rachel; McGee, Rosie; Fox, Jonathan; Anderson, Colin (Institute of Development Studies, 2022)
Multiple aid agencies often try to support change in the same places, at the same time, and with similar actors. Surprisingly, their interactions and combined effects are rarely explored. This Policy Briefing describes findings from research conducted on recent aid programmes that overlapped in Mozambique, Nigeria, and Pakistan, and from a webinar with UK Foreign, Commonwealth & Development Office (FCDO) advisors and practitioners. The research found three distinct categories of ‘interaction effects’: synergy, parallel play, and disconnect. We explore how using an ‘interaction effects’ lens in practice could inform aid agency strategies and programming.
Accepted: 2022-05-10T09:42:35Z